Local Anesthetic Ropivacaine Exhibits Therapeutic Effects in Cancers - Xu, Peng; Zhang, Shaobo; Tan, Lili; Wang, Lei; Yang, Zhongwei; Li, Jinbao (Frontiers in Oncology, 2022)
Despite the significant progress in cancer treatment, new anticancer therapeutics drugs with new structures and/or mechanisms are still in urgent need to tackle many key challenges. Drug repurposing is a feasible strategy in discovering new drugs among the approved drugs by defining new indications. Recently, ropivacaine, a local anesthetic that has been applied in clinical practice for several decades, has been found to possess inhibitory activity and sensitizing effects when combined with conventional chemotherapeutics toward cancer cells. While its full applications and the exact targets remain to be revealed, it has been indicated that its anticancer potency was mediated by multiple mechanisms, such as modulating sodium channel, inducing mitochondria-associated apoptosis, cell cycle arrest, inhibiting autophagy, and/or regulating other key players in cancer cells, which can be termed as multi-targets/functions that require more in-depth studies. In this review, we attempted to summarize the research past decade of using ropivacaine in suppressing cancer growth and sensitizing anticancer drugs both in-vitro and in-vivo, and tried to interpret the underlying action modes. The information gained in these findings may inspire multidisciplinary efforts to develop/discover more novel anticancer agents via drug repurposing.